Incompetence vs. Culpable Non-Performance: The Canadien Arbitration and Adjudication Experience - Knight, Thomas; McPhillips, David; Shetzer, Larry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
Inadequate work performance and incompetence have often been considered by labour arbitrators in Canada within the context of promotion, demotion and transfer cases. However, during the Iast decade these issues have frequently arisen as the primary issues in discipline and discharge cases as well. This paper will begin with a discussion of the legal issues which arise when dealing with performance and incompetence. The following section will set out the data compiled from arbitration awards related to these areas. The next section will set out similar data from adjudication awards in the Federal section. The data from the preceding sections will be analyzed and the paper will conclude with a discussion of the policy implications of the conclusions drawn from the legal issues and the data analyses.